Drinking Water Quality and its Effects on Broiler Chicks Performance During Winter Season - Abbas, Talha E.E.; Elzubeir, Elfadil A.; Arabbi, Omer H. (International Journal of Poultry Science, 2008)
Samples of water were taken from different sources (commercial, Nile and well). Physical, chemical and bacteriological analysis of samples revealed that, levels of salinity, hardness, alkalinity, Ca, Mg, Na and K in the well water were higher than those in the Nile and commercial water. Higher levels of sulphate and chloride were found in the commercial water. Total bacterial count was higher in the Nile water than in the commercial and well water. Then an experiment was carried out to detect the effects of different sources of water on broiler chicks performance and on plasma minerals contents. Broiler chicks given Nile water had significantly increased (P